Disparitas Putusan Pengadilan Negeri Ambon Nomor 32/Pid.Sus-TPK/2021/PN Amb Dengan Putusan Nomor 34/Pid.Sus-TPK/2021/PN Amb - Heidy Mandaku; John Dirk Pasalbessy; Jacob Hattu (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Criminal disparity is a problem that has long been the center of attention of academics. Ambon District Court Decision Number 32/Pid.Sus-TPK/2021/PN Amb with decision Number 34/Pid.Sus-TPK/2021/PN Amb, the formation of the panel of judges is the same. The criminal acts committed were the same at the same time and place, however,but has the aim of analyzing and discussing the differences in the court decisions in the two cases and then discussing and explaining the causes of the differences in the two decisions . The type of research used in this research is normative legal studies. Normative legal research is legal research conducted by investigating literature or secondary data. Data sources used are primary data and secondary data. The data collection technique was carried out, namely searching for and collecting laws and regulations relating to the legal issues encountered. The results of the research showed that the difference in the Court's decision in the PN case in the Court's decision in the Ambon PN case Number 32/Pid.Sus-TPK/2021/PN Amb with decision Number 34/Pid.Sus-TPK/2021/PN Amb is First, the articles granted by the judges are different. II as a Commitment Making Officer (PPK), with the same job, but from the judge's decision for both cases the first decision of the panel of judges used article 2 (unlawful elements) and the second decision used article 3 (abuse of authority).